The Effect Of Job Training, Career Development, And Compensation On Employees Work Ethic At The Gresik Primary Tax Service Office - Rini Purnama Julaeka; Sri Rahayu; Rifda Fitrianty (Lead Journal of Economy and Administration, 2025)
This study aims to examine the influence between job training, career development and compensation on employee work ethic at KPP Pratama Gresik. The sample in this study were 107 employees at the Gresik Primary Tax Service Office. The research data source is a Likert scale questionnaire. The analytical tool used is SPSS, using multiple linear regression analysis. The results showed that partially the variables of job training, career development and compensation had a significant effect on employee work ethic. Then simultaneously the variables of job training, career development and compensation affect the work ethic of employees at the Gresik Primary Tax Service Office.